Factors Influencing Consumer Behavior In An Urban Area - Sundar Kapri, Shyam (International Journal of Psychosocial Rehabilitation, 2019)
Many variables affect consumer behavior. Go-to-market success requires client understanding. "It is crucial to remember that consumer expectations always change due to outside causes (think financial markets catastrophe, layoffs, housing crashes, introduction of the internet), and companies need to be nimble and embrace change to suit customer wants." Consumer purchasing behavior is the final buyer's behavior. Many elements, specificities, and qualities affect the person and the consumer's decision-making process, shopping habits, buying behavior, brands, and merchants. These elements determine a purchase. Consumers are impacted by their culture, subculture, socioeconomic class, membership groups, your relatives, personality traits, psychological characteristics, and social and societal surroundings. Brands can improve their strategy, advertisement (unique value proposition), and advertising campaigns by knowing and comprehending the factors that impact their customers.